+0  
 
0
80
1
avatar

If A = 3^x + 3^{-x} and B = 3^x - 3^{-x}, then find A^2 - B^2.

 Dec 6, 2019
 #1
avatar+109064 
+1

If A = 3^x + 3^{-x} and B = 3^x - 3^{-x}, then find A^2 - B^2.

 

A^2  =  ( 3^x + 3^(-x) )  ( 3^x + 3^(-x) )   =  [ 3^(2x) + 2 (3^x * 3^(-x) ) + 3^(-2x)  ]  =

[ 3^(2x)  + 2  + 3^(-2x) ]

 

B^2  =  ( 3^x - 3^(-x) )  ( 3^x - 3^(-x) )   =  [ 3^(2x) - 2 (3^x * 3^(-x) ) + 3^(-2x)  ]  =

[ 3^(2x)  - 2  + 3^(-2x) ]

 

So

 

A^2   - B^2  = 

 

[ 3^(2x)  + 2  + 3^(-2x) ] -  [ 3^(2x)  - 2  + 3^(-2x) ]  =

 

4

 

 

 

cool cool cool

 Dec 6, 2019

13 Online Users

avatar